Effect of Intradialytic Aerobic Exercise on Relative Blood Volume in Patients Undergoing Maintenance Hemodialysis. Issue 4 (24th June 2021) - Yabe, Hiroki; Kono, Kenichi; Wakayama, Koji; Hanafusa, Norio; Tsuchiya, Ken
Abstract : The purpose of this study was to investigate changes in the relative blood volume because of intradialytic exercise. Twenty patients undergoing hemodialysis (HD) were assigned randomly to exercise or control sessions as a first test by simple randomization. All participants were crossed over and participated in both tests. In the exercise test, each patient underwent 30 minutes of exercise using a cycle ergometer from the initiation of HD. The control session consisted of routine HD without exercise. The blood volume (ΔBV) reduction in both types of sessions was calculated from the area under the curve of the ΔBV (ΔBVAUC ) from the initiation of HD to the end of exercise (During Ex), from the end of exercise to the end of HD (Post Ex), and during the entire HD session (Whole HD). The ΔBVAUC of Post Ex in the exercise test (44.9 ± 14.3%h) was significantly smaller than that in the control test (50.3 ± 14.3%h) ( p  < 0.05), although other parameters such as ΔBVAUC either in the entire HD session or during exercise training did not differ significantly between two groups. This result suggests that intradialytic exercise at the beginning of the HD sessions may be altered the ΔBV in the latter part of the session.